Optimizing the Clerics (Religious Scholars) Role in Actualizing Good Governance Concept - M Muhammadong; St Habibah; Dalilul Falihin; Muhammad Adnan Hudain (International Journal on Advanced Science, Education, and Religion, 2018)
The purpose of this research is to describe the role of the clerics to actualize good governance concept in the development of Makassar City. Therefore, clerics are not merely issuing “fatwas” (religious advises) for the sake of society, but also, clerics can also play a role in development process. The method applied in this research is a descriptive method. While the approach applied is a qualitative method because the issues that are studied are phenomenological. The results show that the role of clerics is optimal in actualizing good governance concept in Makassar City development process. The role and function of the clerics can be represented as a community counselor in line with the government's role as servant and protector of society. Moreover, the policy taken by the government has been supported by all the clerics in actualizing development programs for the mutual good of the societies. In making strategic decisions, clerics sometimes contribute and suggestions to the government to improve social support of that decision